REFLEKS FONEM PROTO AUSTRONESIA PADA BAHASA ACEH - Santoso, Teguh (Fakultas Bahasa, Seni, dan Budaya, Universitas Negeri Yogyakarta, 2005)
Aceh language have similarity with Campa language. So,there are two language which have many similarities vocabulary. Thetheritory of Aceh and Campa is located in the north east of Sumateraisland (Vietnamese). There are Austronesian language grouping.In past, Aceh language have effect from other like Arabic,Netherland, Pourtouguese, Espana, and Chinese.This article explaining the retention and inovation aboutAeh language by reflection of their vocabulary with Austronesiaprotofonem. Austronesian protofonem is the list of the reconstructionof the individual language: Tagalog, Toba-Batak, Java, Malay, Ngaju-Dayak, and Hova. The analysis showed that Aceh language vocal andconsonant have been shift and split in their reflection.Keywords: fonem reflect, proto, inovation, retention